16 blocks - Donner, Richard; Willis, Bruce, 1955-; Mos Def (Rapper); Morse, David, 1953-; Stern, Jenna; Sander, Casey; MacPherson, Glen.; Badelt, Klaus; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2006)
Jack Mosley is a burnt-out detective who is assigned the unenviable task of transporting a fast-talking convict from jail, 16 blocks to the 100 Centre Street courthouse. However, as the two head off, Mosley learns that the man is supposed to testify against Mosley's colleagues, and the entire NYPD want the witness dead. Mosley must choose between loyalty to his colleagues and protecting the witness.
English track: Dolby digital 5.1.
French track: Dolby digital 5.1.
Title from container.
Special features: alternate ending not seen in theaters; deleted scenes with director/screenwriter commentary; theatrical trailer.
Director of photography, Glen MacPherson ; editor, Steve Mirkovich ; music, Klaus Badelt ; costume designer, Vicki Graef ; production designer, Arvinder Grewal ; visual effects supervisor, Evan Jacobs ; special effects supervisor, Marcus Rait.
Bruce Willis, Mos Def, David Morse, Jenna Stern, Casey Sander, Cylk Cozart, David Zayas, Robert Racki.
Keywords: New York (N.Y.). -- Police Dept. -- Drama; Detectives -- New York (State) -- New York -- Drama; Witnesses -- New York (State) -- New York -- Drama; Police corruption -- New York (State) -- New York -- Drama; Criminal behavior -- New York (State) -- New York -- Drama; Feature films; Police films; Action and adventure films; Films for the hearing impaired; Detective and mystery films